Resilience In Christian Leadership: Building A Resilient Community - Dethan, Melly Putriyani; Kleden, Yakobus Beda; Octavianus, Philia; Soinbala, Nusriwan; Modok, Intan (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2025)
Gereja Masehi Injili Di Timor (GMIT) Pengharapan Dendeng is one of the Christian Churches located in Kupang District, Central Kupang Classis, East Nusa Tenggara. In carrying out its ministry, GMIT Pengharapan Dendeng is under the auspices of the GMIT Synod. Advances in technology and social media have brought new challenges, such as issues of identity, social comparison, and digital addiction, which, if not managed properly, can become sources of stress. This has become a particular challenge for both the ministers and congregation of the Church, including the youth of GMIT Pengharapan Dendeng. In response to this situation, the Christian Leadership study program at IAKN Kupang organized a Community Service activity in the form of a workshop titled "Resilience in Christian Leadership: Building a Resilient Community." This Community Service activity aims to strengthen mental and spiritual resilience and build a supportive community. The outcomes of the service provided show that the participants were satisfied and benefited from the Community Service activity, which aims to equip the younger generation with the ability to face life's challenges with strong faith, mental resilience, and an unwavering spirit, while still holding on to Christian values.